2021
DOI: 10.3390/d13090428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ocean Currents in the Western Pacific Ocean on Net-Phytoplankton Community Compositions

Abstract: Phytoplankton are known as important harbingers of climate change in aquatic ecosystems. This study investigated phytoplankton community structure in the western Pacific Ocean (WPO) in 2017 and revealed the spatial variability of phytoplankton in community composition and abundance, as well as their relationship to physical processes and environmental factors. The phytoplankton community was mainly composed of Dinophyta (221), followed by Bacillariophyta (105), Cyanophyta (4), and Chrysophyta (2). The cyanobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Of the small portion of the ASVs that could be annotated, our analysis revealed that Dinoflagellata was the most dominant group of phytoplankton in the Western Pacific seamount regions (Figure 3). This result was not totally surprising because Dinoflagellata was also previously reported to be the most dominant phyla in the Western Pacific regions [16,47], which may be due to environmental factors (including temperature) in these regions [16,48]. However, the relatively high abundance of species in Dinoflagellata estimated by ASVs cannot be simply interpreted as high cell density of these species because the relative abundance of ASVs highly depends on the copy numbers of rDNA genes.…”
Section: Discussionmentioning
confidence: 67%
“…Of the small portion of the ASVs that could be annotated, our analysis revealed that Dinoflagellata was the most dominant group of phytoplankton in the Western Pacific seamount regions (Figure 3). This result was not totally surprising because Dinoflagellata was also previously reported to be the most dominant phyla in the Western Pacific regions [16,47], which may be due to environmental factors (including temperature) in these regions [16,48]. However, the relatively high abundance of species in Dinoflagellata estimated by ASVs cannot be simply interpreted as high cell density of these species because the relative abundance of ASVs highly depends on the copy numbers of rDNA genes.…”
Section: Discussionmentioning
confidence: 67%
“…Current velocity is an environmental parameter that affects phytoplankton. According to Chen et al, (2021), current velocity is very clearly its effect on phytoplankton distribus, not just nutrients, temperature and salinity. The movement of water masses due to currents certainly has an impact on the number of phytoplankton communities that are carried from one water to another.…”
Section: Discussionmentioning
confidence: 99%
“…The thermocline depth in the study area is 100-150 m. The surface seawater possesses high temperature, low salinity and low nutrient content, and is characterized by a two-layer system. A barrier layer separates the nutrient-rich deep water from the surface water (Vinogradov, 1981;Kobayashi and Takahashi, 2002;Chen et al, 2021).…”
Section: Study Areamentioning
confidence: 99%
“…The West Caroline Basin is located in the core of the Western Pacific Warm Pool, where the annual average sea-surface temperature is a minimum of 28°C (Wang et al, 2009;Qi et al, 2020;Chen et al, 2021). Sea temperature anomalies in the region influence climate change in the Asia-Pacific region and even the world by heating seawater and transporting radiant heat to the atmosphere (Long et al, 2021).…”
Section: Introductionmentioning
confidence: 99%